Hematologic improvement with iron chelation therapy in myelodysplastic syndromes: Clinical data, potential mechanisms, and outstanding questions. (September 2019) - Leitch, Heather A.; Gattermann, Norbert
Highlights: MDS are clonal stem cell disorders often requiring red blood cell (RBC) transfusion. RBC transfusion results in iron overload, which portends inferior clinical outcomes. Studies of iron chelation in MDS show hematologic improvement (HI) in some patients. We review clinical data on hematologic improvement with iron chelation therapy in MDS. We review mechanisms by which HI may occur & identify areas for future investigation. Abstract: Myelodysplastic syndromes (MDS) are clonal hematopoietic stem cell disorders characterized by cytopenias and progression to acute myeloid leukemia (AML). Although several treatments for MDS are available, the mainstay of therapy for most patients remains supportive care. This includes red blood cell (RBC) transfusion to correct anemia, which leads to iron overload. RBC transfusion dependence and iron overload portend inferior overall survival. Some studies indicate that iron chelation therapy (ICT) may have beneficial effects on clinical endpoints in MDS; however, these data are from non-randomized trials and the validity of the results is vigorously debated. A consistent observation in clinical studies of ICT in MDS has been hematologic improvement (HI) in some patients, including a reduction in RBC transfusion requirements and even transfusion independence. Here, we review data on HI with ICT in lower risk MDS, preclinical data examining mechanisms by which HI may occur, and identify areas for future investigation.